Gambaran Regulasi Emosi pada Guru BK di SMP Negeri 17 Surakarta - Andressia Yeiza Putri; Dhian Riskiana Putri (Universitas Maritim AMNI Semarang, 2025)
Emotional regulation is an important skill needed by teachers, including guidance and counseling teachers, to face emotional challenges that arise in interactions with students and colleagues. Guidance and Guidance Teachers have a role in supporting students' social and emotional development, so the ability to manage emotions well greatly influences the effectiveness of their performance. The focus of this research is to examine the emotional regulation of guidance and counseling teachers at SMP Negeri 17 Surakarta. A qualitative approach was used with observation techniques and in-depth interviews with a number of guidance and counseling teachers at schools. The research results show that emotional regulation in guidance and counseling teachers involves four main aspects. Guidance and guidance teachers who are able to manage their emotions well will be more effective in providing guidance and counseling to students, reduce stress, and minimize the negative impact of emotional conflict in their work and are able to create a harmonious environment and build good relationships with students.